Analisis Kebutuhan Model Problem Posing Berorientasi STEM - Khairudin Khairudin; Ahmad Fauzan; Armiati Armiati; Karmila Suryani (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2021)
This research is a descriptive survey to determine the needs of lecturers and students for STEM-oriented problem posing learning models that can activate students to ask questions so that students can learn independently and can improve their problem solving skills in calculus. This research sample were students who took Calculus and lecturers who taught calculus. The research instrument used an online needs analysis questionnaire with two forms of statements, namely statements containing qualitative data. The research object consisted of 156 students from Padang State University, Bung Hatta University and STKIP PGRI Padang, as well as 2 lecturers teaching from the three colleges. The results of data analysis showed that on the part of lecturers and students is needed this learning model. Based on this results shows that the importance of designing a multidisciplinary oriented problem posing (STEM) learning model to increase problem solving abilitiesKeywords : Survey research, indicators of needs, level of need for problem posing modelABSTRAKPenelitian ini merupakan survey deskriptif untuk mengetahui kebutuhan dosen dan mahasiswa terhadap model pembelajaran problem posing berorientasi STEM yang dapat mengaktifkan mahasiswa untuk bertanya sehingga mahasiswa dapat belajar secara mandiri dan dapat meningkatkan kemampuan problem solving pada mata kuliah Kalkulus. Subjek penelitian adalah mahasiswa yang mengambil mata kuliah Kalkulus dan dosen yang mengajar Kalkulus. Instrumen penelitian menggunakan angket analisis kebutuhan yang dibuat secara daring yang memuat bentuk pernyataan kualitatif yang dikuantitatifkan. Sampel terdiri atas mahasiswa Universitas Negeri Padang, Universitas Bung Hatta, dan STKIP PGRI Padang berjumlah 141 orang serta dosen yang mengajar dari ketiga perguruan tinggi tersebut masing-masing 2 orang. Hasil analisis data diperoleh bahwa dari pihak dosen dan mahasiswa membutuhkan model pembelajaran problem Posing berorientasi STEM ini untuk meningkatkan kemandirian belajar dan kemampuan problem solving. Kata kunci : penelitian survey, indikator kebutuhan model, tingkat kebutuhan model problem posing.